Manajemen guru dalam meningkatkan kompetensi pengelolaan kelas tahfizh pada pondok pesantren al-hayah jakarta timur - EE.Junaedi Sastradiharja; Khasnah Syaidah; Roswaidah (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2026)
Teachers should ideally possess good classroom management competence, because with this competence teachers are able to create a conducive learning environment, maintain order, reduce problems of student misbehavior, encourage student motivation and achievement, build student participation and collaboration, as well as improve the effectiveness of meaningful teaching and learning processes, so that the development of students’ potential and the learning objectives can be achieved optimally. Teacher management is one way to improve teachers’ competence in managing the classroom. Therefore, this research aims to analyze and discover the effectiveness of teacher management in improving classroom management competence in the tahfizh program at Pondok Pesantren Al-Hayah, East Jakarta. The method used in this research is the survey method with data collection techniques through interviews, observation, and in-depth document studies with the pesantren leaders, Qismul Qur’an, and tahfizh teachers, as well as documentation of teaching and learning activities, while data analysis was carried out through a triangulation approach with the stages of data reduction, data presentation, and conclusion drawing. The results of this research show that teacher management which is adaptive to the cultural context of the pesantren and based on spiritual values has proven effective in improving classroom management competence in the tahfizh program, especially under conditions of limited access to formal education and training